Bovine and human insulin adsorption at lipid monolayers: a comparison - Mauri, Sergio; Pandey, Ravindra; Rzeznicka, Izabela; Lu, Hao; Bonn, Mischa; Weidner, Tobias (Frontiers in Physics, 2015)
Insulin is a widely used peptide in protein research and it is utilised as a model peptide to understand the mechanics of fibril formation, which is believed to be the cause of diseases such as Alzheimer and Creutzfeld-Jakob syndrome. Insulin has been used as a model system due to its biomedical relevance, small size and relatively simple tertiary structure. The adsorption of insu lin on a variety of surfaces has become the focus of numerous studies lately. These works have helped in elucidating the consequence of surface/protein hydrophilic/hydrophobic interaction in terms of protein refolding and aggregation. Unfortunately, such model surfaces differ significantly from physiological surfaces. Here we spectroscopically investigate the adsorption of insulin at lipid monolayers, to further our understanding of the interaction of insulin with biological surfaces. In particular we study the effect of minor mutations of insulin’s primary amino acid sequence on its interaction with 1,2-Dipalmitoyl-sn-glycero-3-phosphoglycerol (DPPG) model lipid layers. We probe the structure of bovine and human insulin at the lipid/water interface using sum frequency generation spectroscopy (SFG). The SFG experiments are complemented with XPS analysis of Langmuir-Schaefer deposited lipid/insulin films. We find that bovine and human insulin, even though very similar in sequence, show a substantially different behavior when interacting with lipid films.